Strategies of political theatre : post-War British playwrights - Patterson, Michael (Cambridge studies in modern theatre., 2003)
This volume provides a theoretical framework for some of the most important play writing in Britain in the second half of the twentieth century. Examining representative plays by Arnold Wesker, John Arden, Trevor Griffiths, Howard Barker, Howard Brenton, Edward Bond, David Hare, John McGrath and Caryl Churchill, the author analyses their respective strategies for persuading audiences of the need for a radical restructuring of society. The book begins with a discussion of the way that theatre has been used to convey a political message. Each chapter is then devoted to an exploration of the engagement of individual playwrights with left-wing political theatre, including a detailed analysis of one of their major plays. Despite political change since the 1980s, political playwriting continues to be a significant element in contemporary playwriting, but in a very changed form.--Publisher description.